Nilai-Nilai Hak Asasi Manusia dalam Prinsip Penyelenggaraan dan Tujuan Pendidikan di Indonesia - Ansori, Miksan (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2016)
Human Rights in education has a strong urgency since education is the main tool for next generation. The implementation of human rights values in education depends very much upon the understanding of human rights by the individuals involved in education. This paper discusses human rights in a variety of perspectives, as well as the values of human rights educational principles and objectives in Indonesia. The existence of human rights in our national educational goal is of course a relief, because with the enforcement of human rights values in our educational objectives, the nature and existence as humans will also be appreciated.